2005
DOI: 10.1021/la0517437
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus atrophaeus Outer Spore Coat Assembly and Ultrastructure

Abstract: Our previous atomic force microscopy (AFM) studies successfully visualized nativeBacillus atrophaeus spore coat ultrastructure and surface morphology. We have shown that the outer spore coat surface is formed by a crystalline array of ~11 nm thick rodlets, having a periodicity of ~8 nm. We present here further AFM ultrastructural investigations of air-dried and fully hydrated spore surface architecture. In the rodlet layer, planar and point defects, as well as domain boundaries, similar to those described for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 61 publications
6
58
0
Order By: Relevance
“…The former finding suggested that the coating layers of the endospores had a pronounced propensity for accumulating the staining dye. Our observation for surface accumulation of ThT was consistent with the abundance of ␤-sheet proteins found on the endospore surfaces (23,(60)(61)(62)(63).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The former finding suggested that the coating layers of the endospores had a pronounced propensity for accumulating the staining dye. Our observation for surface accumulation of ThT was consistent with the abundance of ␤-sheet proteins found on the endospore surfaces (23,(60)(61)(62)(63).…”
Section: Resultssupporting
confidence: 88%
“…These facts provide the rationale of this study for staining endospores with ThT, which targets their endogenous protein structures. The images of the ThT-stained endospores showed bright contours outlining their elliptical shapes, which is consistent with the dye collecting in the surface regions of the spores (where the high ␤-protein content has been demonstrated [60][61][62][63]), and with an increase in the fluorescence quantum yield of the dye bound to these endospore surface regions. Our evidence does not rule out the possibility for weakly fluorescent ThT present in the interior of the stained endospores.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations